Learning L2 by Utilizing Dictionary Strategies: Learner Autonomy and Learning Strategies - Yurike Nadiya Rahmat; Andri Saputra; M. Arif Rahman Hakim; Eko Saputra; Reko Serasi (Lingua Cultura, 2021)
The research aimed to discover what strategies learners employed in using dictionaries and examine the EFL learners’ perspectives in using dictionaries to learn English. Dictionaries were considered meaningful by EFL learners as they were central devices that assisted learning second-language vocabulary. However, not many researchers have investigated the use of these three dictionary strategies in the English for Foreign Language (EFL) context, especially in Indonesia. The data were collected using dictionary strategy questionnaires and semi-structured interviews. One hundred forty-eight students from an Indonesian higher education institution completed a questionnaire survey voluntarily, and then they were selected as samples regarding purposive sampling that typically represented the population. The questionnaire was divided into two parts. The first asked for participants’ personal information and provided several statements from Gu and Johnson about dictionary strategies. The second solicited their opinion about using a dictionary, translated in the Indonesian language. The results show that Indonesian students are aware of how to use dictionaries for comprehension, extended, looking-up strategies, and exploring their beliefs about applying dictionary strategies. These results can help language teachers have a deeper perspective on students’ dictionary strategies in learning so that educators can use those three main dictionary strategies. One such strategy is that teachers can introduce the approaches to their students either implicitly or explicitly by designing meaningful assignments and providing relevant activities and tasks for the students. Therefore, deciding to use a dictionary to overcome the issue is one of the best ways to deal with vocabulary acquisition as it offers more benefits.